2016
DOI: 10.1016/j.ejrad.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of false-positive lesions at interim and end-of-treatment FDG-PET in lymphoma as determined by histology: Systematic review and meta-analysis

Abstract: Both interim and end-of-treatment FDG-PET scans in patients with lymphoma suffer from a very high number of false-positive FDG-avid lesions. This finding, in combination with the previously reported high number of false-negative FGD-PET scans for residual disease detection, suggests that the role of interim and end-of-treatment FDG-PET should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 24 publications
4
57
0
Order By: Relevance
“…Second, we believe the title of their article does not reflect their findings, in which they report FDG‐avidity to be synonymous to residual lymphoma (‘ can residual PET‐positive disease be cured with radiotherapy alone?’ ) despite their finding that 2/3 (66%) of cases of residual FDG‐avid lesions appeared to be false‐positive when biopsy was performed. Note that the high false‐positive rate at response evaluation scans in Hodgkin lymphoma has be reported before (Adams & Kwee, , ), with inflammation being responsible for FDG‐avidity in the majority of cases. The fact that post‐ABVD FDG‐PET results alone have a low positive predictive value (PPV) in predicting disease relapse, and biopsy results do clearly predict a dismal prognosis, suggest that false‐positive results are common at post‐ABVD FDG‐PET scans.…”
mentioning
confidence: 62%
“…Second, we believe the title of their article does not reflect their findings, in which they report FDG‐avidity to be synonymous to residual lymphoma (‘ can residual PET‐positive disease be cured with radiotherapy alone?’ ) despite their finding that 2/3 (66%) of cases of residual FDG‐avid lesions appeared to be false‐positive when biopsy was performed. Note that the high false‐positive rate at response evaluation scans in Hodgkin lymphoma has be reported before (Adams & Kwee, , ), with inflammation being responsible for FDG‐avidity in the majority of cases. The fact that post‐ABVD FDG‐PET results alone have a low positive predictive value (PPV) in predicting disease relapse, and biopsy results do clearly predict a dismal prognosis, suggest that false‐positive results are common at post‐ABVD FDG‐PET scans.…”
mentioning
confidence: 62%
“…The fact that Hodgkin lymphoma is a highly curable disease with a low relapse rate, in combination with the low sensitivity of end‐of‐treatment FDG‐PET, underlines that the number needed to scan (i.e., number of end‐of‐treatment FDG‐PET scans required to detect one case with residual disease) is very high. Furthermore, FDG‐PET scans are expensive, use ionizing radiation, provide patient discomfort, are not available in all institutions and generate false‐positive findings (Adams & Kwee, ; Mesguich et al , ). The latter can have serious consequences, such as unjustified changes in therapy management and prognostication (if histological confirmation of residual FDG‐avid lesions is not performed), result in a high number of unnecessary biopsies, and cause patient anxiety.…”
Section: Results Of Studies On the Sensitivity Of End‐of‐treatment Fdmentioning
confidence: 99%
“…However, both studies had a major (12)(13)(14)(15). Posttreatment and follow-up 18 F-FDG PET/CT studies have a strikingly high number of false-positive results, as has been reported for several lymphoma subtypes (16)(17)(18)(19), including Hodgkin lymphoma (20). Consequently, the studies by Gallamini et al (12,13) are methodologically seriously biased.…”
Section: Replymentioning
confidence: 86%